A comparison of clinical outcomes and cost of radiofrequency catheter ablation for atrial fibrillation with monitored anesthesia care versus general anesthesia. (11th June 2022) - Yokokawa, Miki; Chugh, Aman; Dubovoy, Anna; Engoren, Milo; Jongnarangsin, Krit; Latchamsetty, Rakesh; Ghanbari, Hamid; Saeed, Mohammed; Cunnane, Ryan; Crawford, Thomas; Ghannam, Michael; Liang, Jackson; et al.
Abstract: Introduction: Monitored anesthesia care (MAC) or general anesthesia (GA) can be used during catheter ablation (CA) of atrial fibrillation (AF). However, each approach may have advantages and disadvantages with variability in operator preferences. The optimal approach has not been well established. The purpose of this study was to compare procedural efficacy, safety, clinical outcomes, and cost of CA for AF performed with MAC versus GA. Methods: The study population consisted of 810 consecutive patients (mean age: 63 ± 10 years, paroxysmal AF: 48%) who underwent a first CA for AF. All patients completed a preprocedural evaluation by the anesthesiologists. Among the 810 patients, MAC was used in 534 (66%) and GA in 276 (34%). Ten patients (1.5%) had to convert to GA during the CA. Results: Although the total anesthesia care was longer with GA particularly in patients with persistent AF, CA was shorter by 5 min with GA than MAC ( p  < 0.01). Prevalence of perioperative complications was similar between the two groups (4% vs. 4%, p  = 0.89). There was no atrioesophageal fistula with either approach. GA was associated with a small, ~7% increase in total charges due to longer anesthesia care. During 43 ± 17 months of follow‐up after a single ablation procedure, 271/534 patients (51%) in the MAC and 129/276 (47%) patients in the GA groups were in sinus rhythm without concomitant antiarrhythmic drug therapy ( p  = 0.28). Conclusion: With the participation of an anesthesiologist, and proper preoperative assessment, CA of AF using GA or MAC has similar efficacy and safety.